2013
DOI: 10.1121/1.4812435
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tone training on Cantonese tone-word learning

Abstract: The present study examined the effect of improving lexical tone identification abilities on Cantonese tone-word learning. Native English non-musicians received training on Cantonese tones before learning the meanings of words distinguished by these tones. Their results were compared to English non-musicians and musicians who received no tone training. The tone-trainees obtained a similar level of word identification proficiency as musicians by the end of training and were significantly better than non-tone tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 13 publications
5
24
0
Order By: Relevance
“…This would also suggest that encoding and using phonetic detail when learning similar-sounding words would be improved by decreasing memory demands in the word-learning task (consistent with prior work: e.g., Fennell & Werker, 2003), as well as providing additional support for storing the phonetic detail of word exemplars and forming new phonetic categories. The latter idea is consistent with recent findings that auditory training on difficult phonetic distinctions improves subsequent word learning, and is particularly beneficial for learners with low pre-training auditory sensitivity (Cooper & Wang, 2013; Ingvalson, Barr, & Wong, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…This would also suggest that encoding and using phonetic detail when learning similar-sounding words would be improved by decreasing memory demands in the word-learning task (consistent with prior work: e.g., Fennell & Werker, 2003), as well as providing additional support for storing the phonetic detail of word exemplars and forming new phonetic categories. The latter idea is consistent with recent findings that auditory training on difficult phonetic distinctions improves subsequent word learning, and is particularly beneficial for learners with low pre-training auditory sensitivity (Cooper & Wang, 2013; Ingvalson, Barr, & Wong, 2013). …”
Section: Discussionsupporting
confidence: 90%
“…The lack of relationship between PCPT score and generalization performance highlights older adults’ struggles identifying pitch patterns and using pitch patterns to identify lexical items. Ingvalson et al (2013 ; see also Cooper and Wang, 2013 ) trained younger adults’ with poor baseline sensitivity for pitch patterns to identify pitch patterns prior to introducing lexical training. Those listeners who received the pre-training in pitch identification better learned the lexical categories than those listeners who received the lexical-only training similar to the training used here.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of variability were included in our training stimuli: across conditions, there was variability in the number of speakers (“acoustic variability”), the number of words (“phonetic variability”), and the number of repetitions of different individual tokens. Unlike other high-variability training paradigms that intermixed speakers within the same session (e.g., Perrachione et al, 2011 ; Cooper and Wang, 2013 ), we presented one speaker per day to the listeners in our variable conditions, as in Sadakata and McQueen (2013) , in order to restrict the amount of trial-by-trial acoustic variability given the complex nature of our bisyllabic stimuli. Nevertheless, overall, we manipulated the three types of variability factor (acoustic, phonetic, and repetition) at the same time in order to maximize the contrast between groups with regard to their experience of variability.…”
Section: Discussionmentioning
confidence: 99%
“…Another way would be to identify the main predictor of individual differences in learning and then to directly train that feature. For example, recent studies ( Cooper and Wang, 2013 ; Ingvalson et al, 2013 ) demonstrated that training listeners to perceive pitch directions prior to lexical tone training considerably helps low-aptitude perceivers to improve learning of non-native tonal categories.…”
Section: Discussionmentioning
confidence: 99%